Assessment of primary production using leaf litter of selected mangrove species from Quinapondan, Eastern Samar. - Arceño, Arianne Michelle L. (Tacloban City Arianne Michelle L. Arceno, 2019)
Mangroves are responsible for the primary production in its corresponding ecosystem. One of the factors that determine the amount of primary production in mangrove ecosystems depends on the amount of litterfall. Productivity of a forest may be quantified with the amount of litter produced since these litters determine the components of the organic matter that is deposited from the forest to the surrounding estuary. Quinapondan, Eastern Samar is home to a vast area of mangroves including the mangroves found in Matarinao Bay and in Leyte Gulf. However, an assessment on the primary productivity of the mangrove area have not been studied yet. A transect plot method was used during the assessment of the area. Litter traps and litterbags were placed in selected barangays; Brgy. Buenavista and Brgy. Naga where the Matarinao Bay is located and Brgy. Sto. Niño which is a part of Leyte Gulf. The dominant species present on each station were used for the leaf decomposition experiments using the litter bag method. In Brgy. Naga, Rhizophora apiculata and Lumnitzera lettorea were used. In Brgy. Buenavista, Rhizophora apiculata, Avicennia marina, and Sonneratia alba were used. While in Brgy. Sto. Niño, only Rhizophora apiculata was used since other species were limited. The result of leaf litter decomposition experiments show that S. alba decomposed the fastest followed by L. littorea, A. marina, and R. apiculata, respectively. Colonization of macroinvertebrates were also studied by identification of the fauna present during the retrieval of samples wherein amphipods were the most dominant. The results suggests that the primary productivity of the mangroves of Buenavista and Naga are primarily from the leaves of Sonneratia alba and Lumnitzera littorea, respectively, since the leaves from these species have undergone faster decomposition than the others. Moreover, the slower decomposition of Rhizophora increases its chance of being washed from the coast.